2018
DOI: 10.1002/ajcp.12229
|View full text |Cite
|
Sign up to set email alerts
|

How do Housing Subsidies Improve Quality of Life Among Homeless Adults? A Mediation Analysis

Abstract: Supported housing, combining rent subsidies with intensive case management, is associated with improvements in quality of life of homeless adults, but factors mediating their impact on quality of life have not been studied. Twelve-month outcome data from a randomized trial of the Housing and Urban Development- Veterans Affairs Supported Housing program (HUD-VASH) showed that access to a housing rent subsidy plus intensive case management (ICM) was associated with greater improvement in subjective quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(48 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…Our search yielded 15 908 citations, of which 249 full-text articles were screened, and 72 met inclusion criteria and were included in our systematic review (figure 1; appendix pp [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The 72 articles included data from 15 studies (across 41 publications) on permanent supportive housing, 13,15,17, data from ten studies (across 15 publications) on income assistance, 12,24,[75][76][77][78][79][80][81][82][83][84][85][86][87] and data from 21 publications (of which five publications were also included for the analysis of permanent supportive housing and income assistance) with cost-effectiveness data. 12,13,56,62,72,[88][89][90][91][92][93]...…”
Section: Resultsmentioning
confidence: 99%
“…Our search yielded 15 908 citations, of which 249 full-text articles were screened, and 72 met inclusion criteria and were included in our systematic review (figure 1; appendix pp [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The 72 articles included data from 15 studies (across 41 publications) on permanent supportive housing, 13,15,17, data from ten studies (across 15 publications) on income assistance, 12,24,[75][76][77][78][79][80][81][82][83][84][85][86][87] and data from 21 publications (of which five publications were also included for the analysis of permanent supportive housing and income assistance) with cost-effectiveness data. 12,13,56,62,72,[88][89][90][91][92][93]...…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen of the 55 studies included in this review examined the impact of social relationships on QoL among PEH. Results of these studies showed consistent significant links with QoL and were found to mediate the relationships between independent variables and QoL (M. O'Connell et al, 2018;Rutenfrans-Stupar et al, 2019). Qualitative evidence also supported the importance of social relationships on QoL.…”
mentioning
confidence: 67%
“…Experiences with care, mediated by social participation, had a positive relationship with QoL ([χ 2 = 1.668, comparative fit index [CFI] = 0.961, root mean square error of approximation [RMSEA] = 0.055]; Rutenfrans-Stupar et al, 2019). Housing subsidies, mediated by size of social network, also had a positive relationship with increased QoL ([β = 0.047, 95% CI = [0.005, 0.095]; M. O'Connell et al, 2018). Lack of perceived social support, reported in two studies (odds ratio [OR] = 0.95, 95% CI = [0.91, 0.99], Garey et al, 2019; OR = 2.77, 95% CI = [1.70, 4.49], Ito et al, 2014), associated with negative QoL.…”
mentioning
confidence: 99%
“…Examples of mediation analysis include the effect of genetic variants on the incidence of lung cancer, whether directly and/or mediated through smoking behaviors 1 ; the effect of a new mechanism of drug delivery on quality of life through improved medication adherence 2 ; the effect of a job training program on employment outcomes through the development of new vocational skills and/or job search tools 3 ; and the effect of housing subsidies on quality of life of homeless people that may be mediated through reduced days of homelessness or increased social support 4 …”
Section: Introductionmentioning
confidence: 99%
“…Examples of mediation analysis include the effect of genetic variants on the incidence of lung cancer, whether directly and/or mediated through smoking behaviors 1 ; the effect of a new mechanism of drug delivery on quality of life through improved medication adherence 2 ; the effect of a job training program on employment outcomes through the development of new vocational skills and/or job search tools 3 ; and the effect of housing subsidies on quality of life of homeless people that may be mediated through reduced days of homelessness or increased social support. 4 Traditional mediation analysis estimates the mediation effect through the difference-in-coefficients method 5 or the product-of-coefficients method. 6 In the difference-in-coefficients method, the outcome is regressed on the exposure (with coefficient c) in a first model and on both the exposure (with coefficient c ′ ) and the mediator (with coefficient b) in a second model.…”
Section: Introductionmentioning
confidence: 99%